Acute effects of resistance exercise intensity and repetition at a predetermined volume on inhibitory control: a randomized controlled trial - Chen, Ying-Chu; Lo, Yan-Ho; Hung, Chen-Sin; Cheng, Yi-Ting; Li, Ruei-Hong; Chen, Feng-Tzu; Chang, Yu-Kai (Frontiers in Sports and Active Living, 2025)
BackgroundThis study explores the effects of acute resistance exercise (RE) on inhibitory control (IC), emphasizing exercise volume.MethodsIn total, 78 young adults were randomly assigned to one of three groups: the moderate-intensity group [MI; 60% one repetition maximum (1RM), 3 × 10 reps], the low-intensity group (LI; 30% 1RM, 3 × 20 reps), or the control group (CON; 35 min reading). The exercise groups were volume-matched. Baseline equivalence was assessed via one-way analysis of variance (ANOVA) for demographic variables and chi-square for gender. One-way analysis of covariance examined post-test interreference inverse efficiency score scores, controlling for pre-test values. Two-way ANOVA assessed Group (MI, LI, CON) × Time effects on heart rate (resting; pre-test, during intervention, and post-test), rate of perceived exertion (pre-test, during intervention, and post-test), and lactate (pre-test, mid-test, and post-test). Mean differences and 95% confidence intervals supplemented p-values.ResultsIC was assessed using the Stroop Task, revealing better performance in both the MI (p = 0.026) and LI (p = 0.040) groups compared to CON, though no significant difference was found between the two exercise groups. Blood lactate levels significantly increased post-exercise in both the MI (p = 0.012) and LI (p < 0.001) groups, but again, there was no significant difference between them.ConclusionsThese findings highlight that acute RE, regardless of intensity, enhances IC and raises blood lactate when exercise volume is controlled. Practitioners might tailor RE protocols by adjusting the intensity to match individuals’ capabilities without compromising the cognitive and physiological benefits. Clinical Trial Registrationidentifier (NCT05311202).